2012
DOI: 10.5860/crl-254
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Citation Analysis Methodologies for Collection Management

Abstract: While there is a considerable body of literature that presents the results of citation analysis studies, most researchers do not provide enough detail in their methodology to reproduce the study, nor do they provide rationale for methodological decisions. In this paper, we review the methodologies used in 34 recent articles that present a "user study" citation analysis with a goal of informing collection management. We describe major themes and outliers in the methodologies and discuss factors that require car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 24 publications
0
47
0
4
Order By: Relevance
“…Atıf analizi önemli bir araştırma alanı olup, bir yayından diğer yayınlara yapılan atıfları temel almaktadır. Konu ilişkilerini, yazar etkililiğini, yayım trendlerini anlamak için atıf analizi oldukça kullanışlı (Chikate ve Patil, 2008;Garfield, 1997;Hoffmann ve Doucette, 2012) olmakla birlikte etkili araştırmacıların ya da önemli çalışmaların diğerlerinden daha çok atıf alacağı varsayımına dayanır (Meho, 2007). Bilinen ilk atıf analizi, Pomona Koleji kütüphanesine kazandırılması düşünülen eski ciltleri ve üye olunacak dergileri belirlemek için atıf örüntülerini inceleyen Gross ve Gross (1927) (Amudhavalli, 1997;Giles, Bollacker ve Lawrence, 1998;White, 1985).…”
Section: Introductionunclassified
“…Atıf analizi önemli bir araştırma alanı olup, bir yayından diğer yayınlara yapılan atıfları temel almaktadır. Konu ilişkilerini, yazar etkililiğini, yayım trendlerini anlamak için atıf analizi oldukça kullanışlı (Chikate ve Patil, 2008;Garfield, 1997;Hoffmann ve Doucette, 2012) olmakla birlikte etkili araştırmacıların ya da önemli çalışmaların diğerlerinden daha çok atıf alacağı varsayımına dayanır (Meho, 2007). Bilinen ilk atıf analizi, Pomona Koleji kütüphanesine kazandırılması düşünülen eski ciltleri ve üye olunacak dergileri belirlemek için atıf örüntülerini inceleyen Gross ve Gross (1927) (Amudhavalli, 1997;Giles, Bollacker ve Lawrence, 1998;White, 1985).…”
Section: Introductionunclassified
“…Analisis sitiran merupakan cabang bibliometrika yang meneliti kutipan dalam publikasi seperti jurnal, artikel, dan buku untuk mencari pola penggunaan suatu dokumen (Hoffmann and Doucette, 2012). Analisis sitiran pertama kali ditandai dengan munculnya karya Garfield tahun 1955 berjudul "Citation Indexes from Sciences" sebagai tonggak analisis sitiran pada waktu itu sampai saat ini (SulistyoBasuki, 2002).…”
Section: Analisis Sitiranunclassified
“…13 In addition to the article by Chambers and Healey, several studies have applied both of these elements. Using philosophy dissertations, Jean-Pierre Herubel found that the library held a "strong showing" of 83 percent of the titles cited.…”
mentioning
confidence: 99%